A comprehensive analysis of building energy efficiency policies in China: status quo and development perspective - Li, Jun; Bin, S. (Elsevier Science, 2015)
This article is concerned with a comprehensive analysis of building energy efficiency policies in light of improvements in energy performance, living standards and climate change mitigation in China's built environment. In recent years, China has added about 1.7 billion square meters of new floor space in both urban and rural areas on an annual basis. In 2010, the total area of existing buildings in China was approximately 48.6 billion square meters, nearly twice the total of existing buildings areas in the European Union. How to improve energy efficiency in the soaring number of new buildings and accelerate the retrofit of the huge number of existing buildings are two daunting challenges currently facing China in terms of energy security and climate change mitigation at a global level. China has gradually altered the building energy efficiency policy portfolio, from a purely regulatory approach with a mandatory building code at the initial stage to voluntary green buildings initiatives. This paper is structured as a critical assessment of building energy efficiency policies for new and existing buildings.Both strengths and weaknesses of the implemented energy efficiency policies are detailed in each of the studied areas. It also discusses the dilemma of public games in green and sustainable buildings production in the context of Chinese economic development and societal transition. The analysis emphasises the importance of guaranteeing the consistency between policies in the current regulatory framework to maximise the effectiveness of energy efficiency policies in the built environment in China. For this, it is necessary to articulate building energy efficiency policies implementation and broader energy and climate policies. This integrative study provides both a retrospective assessment and prospective direction of building energy efficiency policy development in China.